Accountable : the true story of a racist social media account and the teenagers whose lives it changed - Slater, Dashka (Farrar Straus Giroux Books for Young Readers, 2023)
"When a high school student started a private Instagram account that used racist and sexist memes to make his friends laugh, he thought of it as "edgy" humor. Over time, the edge got sharper. Then a few other kids found out about the account. Pretty soon, everyone knew. Ultimately no one in the small town of Albany, California, was safe from the repercussions of the account's discovery. Not the girls targeted by the posts. Not the boy who created the account. Not the group of kids who followed it. Not the adults--educators and parents--whose attempts to fix things too often made them worse. In the end, no one was laughing. And everyone was left asking: Where does accountability end for online speech that harms? And what does accountability even mean?" -- Page [2] of cover.